Regorafenib: a promising treatment for hepatocellular carcinoma. (22nd November 2018) - Cerrito, Lucia; Ponziani, Francesca R.; Garcovich, Matteo; Tortora, Annalisa; Annicchiarico, Brigida E.; Pompili, Maurizio; Siciliano, Massimo; Gasbarrini, Antonio
ABSTRACT: Introduction : Hepatocellular carcinoma (HCC) is one of the most frequent malignant tumors with 854, 000 new cases per year and represents the second most frequent cause of cancer-death. Despite surveillance, the number of patients that are diagnosed at a stage in which they are eligible for curative treatments ranges from 30% to 60%. Advanced HCC (BCLC-C) is characterized by a median survival of 6 months. Sorafenib, the first systemic drug proven to be effective in prolonging survival of unresectable HCC, was approved by the FDA in 2007 but no second-line treatment was available for a decade for patients progressing on sorafenib. Finally, in 2016, the RESORCE trial demonstrated regorafenib as an effective second-line treatment. Areas covered : In this manuscript, the authors review the principal preclinical and clinical trials on regorafenib used in the treatment of unresectable HCC patients progressing on sorafenib and highlight both the advantages and the limitations of this drug. Expert opinion : Regorafenib is the only second-line treatment available for patients progressing on sorafenib. Despite its promising clinical application, many doubts still remain, necessitating further investigation to explore the tolerability of this drug in Child-Pugh B and sorafenib-intolerant patients, while its scarce cost-effectiveness must also be improved.